Counseling Regarding The Use Of Social Media As An Entrepreneurship Opportunity Among Secondary School Students At MMA UISU Medan Vocational School - Atika Aini Nasution; M. Asyari Syahab; Rusli Efendi Damanik; Rianto Rianto; Baginda Harahap (Abdimas Paspama, 2024)
Opportunities to run an online business are increasingly opening up, not only for business people, all levels of society can take advantage of this opportunity. Online shopping makes it easier for consumers to shop without spending time and energy. People can take advantage of social media in entrepreneurial activities. Social media has become an interactive marketing tool or tool, a service for building communication with customers and potential customers, as well as a tool for selling and buying products online. Providing exposure regarding counseling on the use of social media as an entrepreneurial opportunity among high school students at SMK MMA UISU Medan .The methods or ways of solving problems used in carrying out this community service are through training/counseling, discussions, and simple application practices regarding social media and entrepreneurship. Before the activity is carried out, the following preparations are made: Carrying out internal activities with the school principal to obtain permission to carry out community service activities. Preparing tools and materials for the presentation of an explanation regarding the use of social media as an entrepreneurial opportunity among high school students at SMK MMA UISU Medan. Determine the place, time and duration of community service activities. The service activities took place on January 11 2022, at SMK MMA UISU Medan. It is hoped that this activity will be useful for students of SMK MMA UISU Medan so that they are able to instill an entrepreneurial spirit and can use social media wisely and be able to take advantage of the opportunities that exist around them, so that it is very helpful in opening up employment opportunities and improving a better standard of living.